PERANAN PENGAWASAN PIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI SUMATERA BARAT - David Ardi Marta; Efni Cerya; Syamwil Syamwil (Universitas Negeri Padang, 2018)
This study aims to examine: (1) Influence Supervision of Leadership and Work Discipline on Employee Performance,(2) Supervision of Leadership on Employee Performance (3) Influence of Work Discipline on Employee Performance of Education Office of West Sumatera Province. The type of this research was descriptive associative. The population in this study amounted to 276 people. The sampling technique used was Propotional Random Sampling. Data of this research was primary data with research instrument in the form of questionnaire which have been tested for validity and reliability. Further data analyzed by using multiple regression analysis with SPSS. Based on the results of the study, it was advisable Provincial Education Office of West Sumatra to be better again in improving the performance of employees, especially in terms of commitment in the employee to be more improved so that it can be have an impact on the improving employee performance. It then increases Leadership Supervision in comparing employee job results to predefined standards for feedback on the work they undertake. Employee Discipline to be more improved especially in the case of compliance with work standards that is by taking into account the standards and time set by the Education Office of the Province of West Sumatra for work done in line with organizational goals and can be completed in a timely manner. Keywords: Leadership Supervision, Work Discipline and Employee Performance